Chemistry (Hess's Law)

posted by .

NO2(g) → 1⁄2N2(g) + O2(g) ΔH1 = -33.9 kJ

NO2(g) → NO(g) + 1⁄2O2(g) ΔH2 = 56.5 kJ

What is ΔH for the reaction 1⁄2N2(g) + 1⁄2O2(g) → NO(g) ?

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. chemistry

    Use the standard reaction enthalpies given below to determine ΔH°rxn for the following reaction: 2 NO(g) + O2(g) → 2 NO2(g), ΔH°rxn = ?
  2. Chemistry

    Given the following hypothetical equations, 2A + B → 3C + 2D ΔH = -46.7kJ C → B ΔH = 13.1kJ 2E → B ΔH = 84.5kJ, what is the enthalpy change (kJ) for the following reaction?
  3. Chemistry - Thermodynamics

    Which one of the following reactions would you expect to have highest ΔS°?
  4. Chemistry

    Calculate the enthalpy change for the reactions NO(g) + O(g) → NO2(g) from the following data: NO(g) + O3(g) → NO2(g) + O2(g) ΔH = -198.9 kJ O3(g) → 1.5O2(g) ΔH = -142.3 kJ O2(g) → 2O(g) ΔH = …
  5. Chemistry

    Given 2Al(s) + 3/2O2(g) → Al2O3(s), ΔH°f = -1,670 kJ/mol for Al2O3 (s). Determine ΔH° for the reaction 2Al2O3(s) → 4Al(s) + 3O2(g).
  6. Chem

    Set up a Hess’s law cycle, and use the following information to calculate ΔH∘f for aqueous nitric acid, HNO3(aq). You will need to use fractional coefficients for some equations. 3NO2(g)+H2O(l)→2HNO3(aq)+NO(g) ΔH∘ …
  7. Chemistry

    Please help me! I don't know how to do this at all. Calculate the enthalpy for the reaction: NO (g) + O (g) → NO2 Given the following known reactions: NO(g)+O3 (g)→NO2 (g)+O2 (g) 03 (g)→1.5O2 (g) O2 (g)→2O(g) …
  8. algebra math

    Which one of the following is a geometric sequence?
  9. Chemistry

    Enthalpy Change Given the following reactions: S(s) + O2(g) → SO2(g) ΔH = -297 kJ/mol SO2(g) + ½ O2(g) → SO3(g) ΔH = -141 kJ/mol Calculate the ΔH for the reaction: S(s) + 3/2O2(g) → SO3(g)
  10. AP Chemistry

    Calculate ΔHrxn for the following reaction: C(s)+H2O(g)→CO(g)+H2(g) Use the following reactions and given ΔH values: C(s)+O2(g)→CO2(g), ΔH= -393.5 kJ 2CO(g)+O2(g)→2CO2(g), ΔH= -566.0 kJ 2H2(g)+O2(g)→2H2O(g), …

More Similar Questions